Heat capacity and glass transition in P2O5-H 2O solutions: Support for Mishima's conjecture on solvent water at low temperature - Corti, Horacio Roberto (2011)
The P2O5-water system has the widest range of continuously glass-forming compositions known for any glassformer + water binary system. Despite the great range of structures explored by the glasses and liquids in this system, the glass transition temperature (Tg) itself varies in a simple monotonic fashion. However the values of Tg reported in the literature show wide disagreement, linked to the different methods of measurement employed. In this work we use differential scanning calorimetry (DSC) to obtain both Tg itself and the jump in heat capacity that occurs as the metastable equilibrium of the supercooled liquid relieves the non-ergodic glassy state. Our study covers the molar ratio range of H2O/P2O5 from 1.5 to 14 (corresponding to the mass fraction of P2O5 between 0.36 and 0.84), which includes the compositions corresponding to pyrophosphoric acid (H 4P2O7) and orthophosphoric acid (H 3PO4). The theoretical model of Couchman and Karasz predicts very well the glass transition temperatures of the P2O 5-H2O system over the whole composition range if the relatively large heat capacity change associated with water in aqueous solutions at the glass transition temperature is adopted, instead of the vanishingly small value observed for vapor deposited or hyperquenched pure water. Therefore, solvent water in this ambient pressure P2O5-H 2O system behaves like a different liquid, more closely resembling a high-density liquid (HDL) polyamorph, as suggested by Mishima for electrolytes at high pressures.